Parental perspectives on the quality of life of children with Down syndrome - Fucà, Elisa; Galassi, Paolo; Costanzo, Floriana; Vicari, Stefano (Frontiers in Psychiatry, 2022)
Down Syndrome (DS) is the most common chromosome abnormality and the most frequent cause of developmental delay/intellectual disabilities in children. Although the investigation of the quality of life (QoL) is crucial in children with DS, relatively poor attention has been paid to this topic. The current study aimed to evaluate parent-reported QoL in a group of children with DS and identify children's individual and clinical features associated with different levels of QoL. We included in the study 73 children with DS (5–12 years) and investigated the parent-reported levels of QoL by means of the Pediatric Quality of Life Inventory. Cognitive level and the presence of behavioral difficulties were also evaluated. The overall parent-reported QoL of children with DS was high; emotional functioning was the domain with the highest level of QoL. Moreover, parents perceived low levels of QoL in children who exhibited low IQ, worse analogical reasoning, worse adaptive skills, more frequent challenging behaviors, more ritualistic/sameness behavior and more autistic symptoms. No differences emerged for family variables, namely parental education and employment, between the two groups with high and low QoL, as perceived by parents. The understanding of cognitive and behavioral factors - such as analogical reasoning, socio-communication abilities and challenging behaviors - related with different degrees of QoL in children with DS is crucial for the development of effective strategies to promote the improvement of the QoL.